ANALISA PELAKSANAAN PENINGKATAN PENGHASILAN MELALUI SUPPORT INDUSTRI KECIL MENENGAH BATU BATA DI DESA BLOK-15 KABUPATEN ACEH SINGKIL - Imsar, Imsar; Syarvina, Wahyu; Sumi, Raudatun (Jurnal Ekonomi Manajemen, 2023)
This study aims to determine the implementation of increasing the income of the small and medium brick industry in Blok-15 Village, Aceh Singkil District, to find out how the government's efforts to support the implementation of small and medium industries in Blok-15 Village, Aceh Singkil District, and to find out how the efforts of activists bricks handle raw material shortages in Blok-15 Village, Aceh Singkil District. This research is a qualitative descriptive study. The data collection technique used was interviewing several brick activists, Pj. The Head of Blok-15 Village is accompanied by several Heads of Lorong Village Blok-15. Observations and documentation were carried out at the location of the small and medium brick industry in Blok-15 Village, Aceh Singkil District. The results of the research that have been obtained are that the implementation of increasing the income of the small and medium brick industry has been carried out well, but there are several obstacles that have become obstacles for them, namely the difficult supply of raw materials and until now there has been no government effort to support the industry which is the hope for activists. Both in terms of facilities and other. Then in an effort to deal with the current shortage of good raw materials it has been carried out effectively. If the supply of raw materials is always met, then activists will have no difficulty in producing these bricks again so that the needs of each household are met. Therefore, the role of government as a facilitator here is very much needed.